Answer:
-2
Step-by-step explanation:
hi! to find f(-3) on this graph, go to the x-value -3 and find the y-value there. when we look at -3 on the x-axis, we go down and see that there is a point at (-3,-2). therefore, f(-3)=-2.
Answer:
i need an picture then I will help you out
Step-by-step explanation:
This can be solved by Newton's binomial formula
Tk+1 = (n k) a∧(n-k) b∧k k+1=7 => k=6, n=11 , a=-3x and b=-2y
T7= (11 6) (-3x)∧(11-6) (-2y)∧6 = (11*10*9*8*7)/(1*2*3*4*5) (-3x)∧5 (-2y)∧6
T7= 462 (-3x)∧5 (-2y)∧6
The correct answer is A.
Good luck!!!
Answer:
253.5
Step-by-step explanation:
basically i had the same question so yeah! and im a pro at math
Answer:
74-25 is 49
Step-by-step explanation: